The Weighted $L^p$-Boundedness for a Class of Multilinear Oscillatory Singular Integrals Related to Block Spaces (Analysis in Theory and Applications, 2024)
This paper obtains a criterion on the weighted $L^p$-boundedness for a classof multilinear oscillatory singular operators with real-valued polynomial phases andrough kernels belonging to the block spaces.